Construction of initial national quasi-geoid model VIGAC2017, first step to national spatial reference system in Vietnam - Hoa, Ha Minh (Vietnam Journal of Earth Sciences, 2017)
84 reference ellipsoid. However, usage of the broadcast satellite messages doest not give high accuracy in determination of national quasi-geoid heights. Based on the determined geopotential of the Hon Dau local geoid and constructed initial mixed quasi-geoid model VIGAC2014, this scientific article presents results of building of initial national quasi-geoid model VIGAC2017. Used data consisting of geodetic coordinates B, L, H of 164 first and second orders benchmarks of the national leveling networks was obtained from GPS data processing in ITRF according to global WGS-84 ellipsoid with satellite ephemeris accuracy at level of ± 2,5 cm, and the initial mixed quasi-geoid model VIGAC2014 was constructed from the EGM2008 model. The orientation of the WGS-84 ellipsoid was accomplished under conditions of it’s best fitting to the Hon Dau local quasi-geoid and the parallelism of its axes to the corresponding axes of the national WGS-84 reference ellipsoid allows get national quasi-geoid heights and coordinate transformation parameters that have been used for conversion of the mixed quasi-geoid heights from the VIGAC2014 quasi-geoid model to the initial national quasi-geoid model VIGAC2017. Along withquasi-geoid heights which were obtained from the initial national quasi-geoid model VIGAC2017, an estimation of the accuracy of differences ( ) shows that quasi-geoid heights have the accuracy at the level of ± 6,2 cm. Apart from that determination of seven coordinate transformation parameters leads to the building of the initial national spatial reference system in Vietnam. References Bursa M., Kenyon S., Kouba J., Sima Z., Vatrt V., Vitek V., Vojtiskova M., 2007. The geo-potential value W0 for specifying the relativistic atomic time scale and a global vertical reference system. Journal of Geodesy, 81(2), 103-110. Gauss, C.F., 1828. Bestimmung des Breitenunterscchiedes zwischen den Sternwarten von Gottingen und Altona, Gottingen. Ha Minh Hoa, Dang Hung Vo, Pham Hoang Lan, Nguyen Ngoc Lau, 2005. Research scientific base for construction of different orders GPS networks in dynamic reference system. General report of the science - technological teme of the Ministry of Natural Resources and Environment in period 2002 - 2004, Hanoi. Ha Minh Hoa et al., 2012. Research scientific base for perfection of the height system in connection with construction of national dynamic reference system. General report of the science - technological teme of the Ministry of Natural Resources and Environment. Hanoi. Ha Minh Hoa, 2013a. Method of coordinate transformation bewwen coordinate systems. Science and Technique Publisher, Hanoi, 140p. Ha Minh Hoa, 2013b. Estimating the geo-potential value W0 of the local geoid based on data from local and global normal heights of GPS/Leveling points in Vietnam. Geodesy and Cartography. Taylor & Francis. UDK 528.21, doi:10.3846/20296991.2013.823705, 39 (3), 99-105. Ha Minh Hoa, 2013c. Problems related to construction of national spatial reference system. Journal of Geodesy and Cartography, 18, 1-10. Vietnam Institute of Geodesy And Cartography. Ha Minh Hoa, 2014a. Method of mathematical processing of national geodetic networks. Science and Technique Publisher, 244p, Hanoi. Ha Minh Hoa, 2014b. Theory and practice of geodetic gravimetry. Science and Technique Publisher, Hanoi, 592p. Ha Minh Hoa, Nguyen Thi Thanh Huong, 2015a. Research for perfection of method of mathematical processing of first, second orders leveling network in modern height system in Vietnam. General report of the science - technological teme of the Ministry of Natural Resources and Environment in period 2012-2015, Hanoi. Ha Minh Hoa, Nguyen Tuan Anh, 2015b. Effective realization of correction of spherical harmonic coefficients of Earth gravitational model by mothod of Colombo O. L. Journal of Geodesy and Cartography, 25, 25-32. Vietnam Institute of Geodesy And Cartography. Ha Minh Hoa, Nguyen Ba Thuy, Phan Trong Trinh et al., 2016a. Research for determination of normal surfaces of sea levels (“zero” depth surface, mean sea surface, highest sea surface) by methods of geodesy, hydrography and geology with serving construction of buildings and planning of coastline in tendency of climate changes”. State techno - scientific theme with code KC.09.19/11-15 in period of 2011-2015. Vietnam Ministry of Science and Technology, Ha Noi. Ha Minh Hoa, 2016b. Research of height changes between Hon Dau local quasi-geoid and global quasi-geoid in the world scale. Journal of Geodesy and Cartography, 28, 1-7. Vietnam Institute of Geodesy And Cartography. International Association of Geodesy (IAG), 1984. IAG Resolutions adopted at the XVIII General Assembly of the IUGG in Hamburg, August 1983. “The Geodesist’s handbook”. Bulletin Geodetique, 58(3), p.321. Listing, J.B., 1873. Ueber unsere jetzige Kenntuts der Gestalt und Grösse der Erde. Nachrichten von der Georg - Augusts Universi tät, Gröttingen, (3), 33-98. Le Huy Minh, Tran Thi Lan, R. Fleury, C. Amory Mazaudier, Le Truong Thanh, Nguyen Chien Thang, Nguyen Ha Thanh, 2016. TEC variations and ionosphere disturbances during the magnetic storm in March 2015 observed from continuous GPS data in the Southeast Asia region. Vietnam Journal of Earth Sciences, 38(3), 287-305. Luong Thanh Thach, 2016. Accuracy estimation of the initial national quasi-geoid model VIGAC2014 based on 75 second order benchmarks. Journal of Geodesy and Cartography, 25, 17-28. Vietnam Institute of Geodesy And Cartography. Nguyen Tuan Anh, 2015. Detailed research of height of Hon Dau local geoid according to the global geoid in territory of Vietnam. Journal of Geodesy and Cartography, 25, 33-38. Vietnam Institute of Geodesy And Cartography. Petit, G., Luzum, B., 2010. IERS Conventions, 2010. IERS Technical Note, 36, Verlag dés Bundesamts fur Kartographie und Geodasie. Frankfurt am Main 2010, 179p. Scientific report. Construction of national coordinate system and reference system, 260p. General Department of Land Adminustration, Hanoi. Vy Quoc Hai, Tran Quoc Cuong, Nguyen Viet Thuan, 2016. Crustal movement along the Red river fault from GNSS data. Vietnam Journal of Earth Sciences, 38(1), 14-21.